Spatial extent and consequences of black bass (Micropterus spp.) invasion in a Cape Floristic Region river basin. Issue 4 (30th November 2015) - Van Der Walt, Johannes A.; Weyl, Olaf L. F.; Woodford, Darragh J.; Radloff, Frans G. T.
Abstract: Black bass ( Micropterus spp.) are invasive fish that have adversely affected native fish communities in many regions of the world. They are known to threaten native fishes in the Cape Floristic Region of South Africa, a fish endemism hotspot, but the extent of invasion and consistency of impacts at river basin scales are not known. This study investigated the extent of black bass invasions in 41 tributaries in the Olifants–Doorn River basin (ODR) using above‐water observations, snorkel surveys and underwater video assessment. Physical barriers that defined the upper limit of black bass distributions in tributaries were measured. Black bass impacts on the densities and diversity of the native fish fauna across the basin were assessed. Black bass were found to have invaded 81% of stream habitat in the basin, with Micropterus dolomieu and Micropterus punctulatus consistently being blocked by physical barriers in the form of waterfalls, cascades and chutes. These barriers had a minimum height of 49 cm and a median height of 1.09 m. Small‐bodied cyprinid minnows ( Barbus calidus and Pseudobarbus phlegethon ) were consistently extirpated from black bass‐occupied reaches, while larger cyprinid species co‐occurred with black bass, but only when they were larger than 10 cm. These findings demonstrate the severe habitat loss to native fishes as a result of black bass invasion, and the prevention of the further spread and removal of black bass from these rivers should be a high conservation priority. The study demonstrates the critical role physical barriers play in preventing the extinction of native fish species and provides a basis for the planning of conservation interventions such as the construction of in‐stream invasion barriers. Copyright © 2015 John Wiley & Sons, Ltd.